Influence of Geogrid Reinforcement on Lateral Earth Pressures Against Model Retaining Walls. Issue 3 (1999) - Tsukamoto, Y.; Ishihara, K.; Higuchi, T.; Aoki, H.
Abstract : Large-scale model retaining wall tests were carried out using reinforced and unreinforced granular backfill and geogrid layers that were not attached to the wall facing. The objective of this study was to observe the lateral earth pressures on the model retaining walls under a range of surcharge pressures, which ranged from an at-rest to active-state condition. In so doing, the effectiveness of unattached geogrid reinforcement layers in reducing the lateral earth pressures was demonstrated. It was shown that unattached geogrid layers effectively reduce the coefficient of active earth pressure. The coefficients of earth pressure at rest, Ko, and at an active state, Ka, were examined, and the formulation of the coefficient of earth pressure-displacement curve was proposed. Interface shear stresses induced along the geogrid layers were also examined under different surcharge pressures. An apparent coefficient of lateral stress for the geogrid reinforcement was defined and compared with the corresponding coefficient of earth pressure. In addition, by measuring lateral stresses at several locations on the side walls of the model soil container, the changes in the out-of-plane stresses were examined.